Effect of misoprostol as an adjunct to oxytocin during caesarean delivery in women at risk of postpartum hemorrhage - Yusof, Mudirah Mohd (2017)
Introduction: The caesarean section was a recognized risk factor for PPH. The common cause of PPH during caesarean delivery includes uterine atony result in complications including both maternal and fetal morbidity and mortality. Oxytocin is the first choice of uterotonic agent for prevention of PPH during caesarean delivery. The use of additional uterotonic agent is common in women with known risk factor for PPH. Misoprostol has been evaluated as an alternative to oxytocin and has also been used in combination with oxytocin. Objectives: To evaluate whether a combination of misoprostol and oxytocin more effectively reduces blood loss during and after caesarean delivery than does oxytocin alone among women with known risk factors for postpartum hemorrhage. To document the use of additional uterotonic drugs, the need of blood transfusion or additional surgical intervention for PPH and to identify the complication and adverse effects related to drugs therapy.Methodology: A prospective single blinded randomised control trial was conducted in Hospital Raja Perempuan Zainab II from December 2016 until April 2017. The study included 156 women with known risk factor for PPH undergoing elective caesarean section under spinal anaesthesia. They were assigned randomly into 2 groups to receive either sublingual misoprostol 400mcg+ IV oxytocin 5 IU bolus or IV oxytocin 5 IU bolus just after delivery of baby. The outcome measures were intraoperative and postoprerative blood loss, reduction in haemoglobin, additional uterotonic agents, blood transfusion, additional surgical intervention for PPH and adverse effects relate to drugs therapy. Results: A total of 156 women were recruited and completed this study. The maternal demographic data and risk factors were similar between the 2 groups. The mean for preoperative haemoglobin was 11.3 g/dl in misoprostol+oxytocin group compared to 11.5 g/dl in oxytocin group. The range of preoperative haemoglobin was 8.1-14.1 g/dl. The estimated blood loss intraoperatively in oxytocin group was statistically significantly higher than the misoprostol+oxytocin group (654.5 ml±259.9 versus 524.3ml±253.9, p = 0.010). Estimated blood loss postoperatively in oxytocin group was statistically significantly higher than the misoprostol+oxytocin group (90 ml±29.6 versus 77.1 ml±23.7, p =0.003). It also showed statistically significant higher number of PPH seen in oxytocin group compared to misoprostol+oxytocin group (19(24.4%) versus 9(11.5%), p= 0.037). The incidence of PPH in this study was 17.9%. Out of 19 patient with PPH in oxytocin group, 7 (36.8%) patients required additional single dose IM hemabate 250 mcg compared to misoprostol group, only 2 (22.2%) patients required single dose IM hemabate 250mcg. Only 4 patients with PPH required blood transfusion. However, no significant difference was demonstrated between the 2 groups in term of reduction in hemoglobinlevel (p=0.750), any additional uterotonic drug (p=0.083) and blood transfusion (p=0.310). No additional surgical intervention required for both groups. Conclusion: Combination of sublingual misoprostol and oxytocin more effectively reduces blood loss during and after caesarean delivery than does oxytocin alone among women with risk factors for PPH. It also appears safe and well tolerated in this population. Therefore misoprostol should be considered as a good alternative to other uterotonics in prevention of PPH following caesarean delivery.